2017
DOI: 10.1080/02813432.2017.1333319
|View full text |Cite
|
Sign up to set email alerts
|

Threats or violence from patients was associated with turnover intention among foreign-born GPs – a comparison of four workplace factors associated with attitudes of wanting to quit one’s job as a GP

Abstract: ObjectiveGeneral practitioners (GPs) are crucial in medical healthcare, but there is currently a shortage of GPs in Sweden and elsewhere. Recruitment of GPs from abroad is essential, but foreign-born physicians face difficulties at work that may be related to turnover intention, i.e. wanting to quit one’s job. The study aims to explore the reasons to why foreign-born GPs may intend to quit their job.DesignSurvey data were used to compare four work-related factors that can be associated with turnover intentions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
4
30
0
Order By: Relevance
“…[5][6][7][8][9] In addition, WPV has a negative impact on the retention of healthcare workers and the quality of medical care. [10][11][12] Healthcare workers are the main providers of healthcare services and the foundation of any healthcare system. The efficiency, effectiveness and quality of a nation's healthcare system are directly associated with the quality and size of its healthcare workforce.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] In addition, WPV has a negative impact on the retention of healthcare workers and the quality of medical care. [10][11][12] Healthcare workers are the main providers of healthcare services and the foundation of any healthcare system. The efficiency, effectiveness and quality of a nation's healthcare system are directly associated with the quality and size of its healthcare workforce.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study showed that foreign‐born health care professionals more frequently experience a lack of social support at work and work‐related distress than native nurses (Aalto, Heponiemi, Keskimaki, et al, ). Moreover, it has been shown that the risk of violence from patients and colleagues is higher among migrant health care employees (Crutcher, Szafran, Wolochuk, Chatur, & Hansen, ; Eneroth, Gustafsson Senden, Schenck Gustafsson, Wall, & Fridner, ). Health care professionals of foreign origin have also been reported to experience social isolation in the workplace (Chen et al, ) and to be at an increased risk of discrimination (Schilgen, Nienhaus, Handtke, Schulz, & Mosko, ).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign-born physicians may face more insensitivity, discrimination and isolation in their workplace [ 7 , 8 ]. For example, foreign-born physicians had higher levels of threats or violence from patients compared to native physicians in Sweden [ 9 ] and foreign-born physicians have been found to face harassment from their colleagues [ 10 ]. Foreign-born physicians working in Germany have reported discrimination, difficulties in interpersonal interactions and a lack of setting-specific (language, cultural, clinical and system) knowledge [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there might also be factors that could attenuate these risks. For example, control over one’s job has been suggested to be especially important for foreign-born physicians [ 9 ]. Job control has been associated with lower turnover intention among foreign-born physicians [ 9 ] and it has been found to ease the potential challenges coming from working in culturally diverse teams [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation